SOLUSI MENGHADAPI KEKERASAN PADA ANAK DALAM PENDIDIKAN - Widowati, Nina (FORUM, 2011)
Abstract :Children are the world's most valuable resource and its best hope for the future of a family and a nation. They have a very important role in guaranteeing the existence of nation in the future. In order to produce high quality generation who can responsible optimally, they need to get chance to grow anddevelop physically, mentally, socially and spiritually. Ironically, children often become object of violence done by educator(parent, teacher, babysitter, etc) who may do violence consciously or unconsciously. In this kind of situation, child abuse happened simultaneously that might cause generation crisis. 'Ratification of Rights of the Child' has protected them from those minor position that endanger the children. In order to support the ratification, teachers are expected to provide more appreciation to student by doing the following method; engaging, activating, sharing and empowering and also by implementing '3P' which is focusing on the activity of provision, protection and participation.Keywords : child abuse, child friendy teaching modelpermalink: http://ejournal.undip.ac.id/index.php/forum/article/view/3156